USING A CACO-2 AND THP-1 CO-CULTURE MODEL TO EVALUATE INTESTINAL BARRIER PROTECTIVE PROPERTIES — EFFECTS OF DEXAMETHASONE - Riedel, Sylvia; Engelbrecht, Lize; Venter, Pieter; Louw, Johan; Pheiffer, Carmen; Muller, Christo J.F. (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Increased intestinal permeability or so-called “leaky gut,” is considered an early event in the development of obesity and diabetes. It is likely driven by the translocation of bacteria-derived products such as lipopolysaccharide (LPS) from the intestinal lumen into the blood stream leading to low-grade inflammation. A co-culture model of intestinal barrier dysfunction was used to characterize the mechanisms of barrier protection induced by an anti-inflammatory drug METHODOLOGY In co-cultured CACO-2 and THP-1 cells representing the intestinal epithelium and immune cells, respectively, barrier dysfunction was induced using LPS and quantified by measuring trans-epithelial electrical resistance (TEER). Dexamethasone was tested for its barrier-protective properties by application to the apical side. Dexamethasone concentration was quantified on apical and basolateral sides after 24-hour treatment using liquid chromatography/mass spectrometry. Cytokine release was determined using a multiplex chemiluminescence assay (mesoscale discovery). Expression of selected tight junction (TJ) proteins was assessed using immunocytochemical staining and confocal imaging. RESULTS Dexamethasone significantly (p=0.009) improved TEER by 30%, while 74% of the dexamethasone remained on the apical side and 24% was detected basolaterally. Dexamethasone significantly decreased interleukin (IL)-6 (p<0.0001), tumour necrosis factor α (p<0.0001) and IL-1β (p=0.051) release by THP-1 cells. However, confocal imaging revealed that dexamethasone did not improve the localization of occludin, claudin-2 or zonula occludens-1 when compared to LPS-induced cells. CONCLUSION Dexamethasone improved barrier function likely due to its anti-inflammatory effect. However, it could not prevent localization of the pore-forming claudin-2, which may explain the presence of residual barrier dysfunction in this model.